ENGAGEMENT OF CHILDREN WITH DISABILITIES IN FESTIVE EVENTS IN AN ADAPTED MOTOR ACTIVITY PROGRAM (Fiep Bulletin - online, 2016)
The aim of this research was to analyze the involvement of children with disabilities in the activities proposed during festive occasions in a program of Adapted Motor Activity. For data collection, was used the shooting of the event (June festival) in two consecutive years and the description of the activities minute-by-minute. It was considered the occupancy time of each station (play). The events were divided in four periods: a. Playing at the stations; b. Typical dance; C. Typical food; d. Return to play. All participants engaged in the activities and it was possible to highlight how happy the children were by watching their parents play.
Keywords: children with disabilities; festive event; engagement time.